2012
DOI: 10.4103/0970-9290.102221
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the level of tumor necrosis factor-α in gingival crevicular fluid and serum in periodontal health and disease: A biochemical study

Abstract: It remains a possibility that the absence or low levels of TNF-α in GCF might indicate a stable lesion and elevated levels might indicate an active site but only longitudinal studies taking into account, the disease "activity" and "inactivity" could suggest the possibility of using TNF-α in GCF as an "Indicator" of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 0 publications
6
33
1
2
Order By: Relevance
“…In periodontal disease, TNF-α levels rise, and TNF-α is held responsible for bone destruction, especially in inflammatory conditions [35]. In some studies, high TNF-α levels were reported in gingivitis as well as in periodontitis [36,37]. Similarly, in our study, TNF-α levels were found to be higher in gingivitis and periodontitis compared to those of the healthy control group, while there was no difference between gingivitis and periodontitis.…”
Section: Discussioncontrasting
confidence: 53%
“…In periodontal disease, TNF-α levels rise, and TNF-α is held responsible for bone destruction, especially in inflammatory conditions [35]. In some studies, high TNF-α levels were reported in gingivitis as well as in periodontitis [36,37]. Similarly, in our study, TNF-α levels were found to be higher in gingivitis and periodontitis compared to those of the healthy control group, while there was no difference between gingivitis and periodontitis.…”
Section: Discussioncontrasting
confidence: 53%
“…In other studies there was substantial elevation in TNF- α concentration from healthy to diseased sites [14, 70, 91]. Thus, TNF- α concentrations may also be used as a predictor of disease progression.…”
Section: Discussionmentioning
confidence: 90%
“…Reis et al [91] showed that TNF- α levels were significantly higher in diseased sites compared to nondiseased sites. Gokul [14] showed a highly significant difference between healthy subjects and patients with gingivitis and CP. Kurtiş et al [70] showed highly significant difference between healthy subjects and patients with CP and GAgP.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to our study, Reis et al considered only PPD to define chronic periodontal disease while it was unclear what criteria was used for non‐diseased sites. Gokul et al compared gingivitis, chronic periodontitis, and healthy individuals showing significantly elevated levels of TNF‐α in gingivitis and chronic periodontitis groups when compared to healthy subjects, while no significant differences were detected between gingivitis and periodontitis groups …”
Section: Discussionmentioning
confidence: 99%